Negracha: Innovative Aspects in Osvaldo Pugliese’s Tango. (Revista Argentina de Musicología, 2018)
In this article we study Osvaldo Pugliese’s piece Negracha (1947), an example of one of the possible configurations of tango’s musical modernity in its “Golden Age” (1940s), an issue that has been neglected in the realm of musicological research. We make a contextualization of the composer’s work, then a descriptive analysis of some key aspects of the piece and, lastly, some general comments on aesthetic issues. We research the creative processes present in the composition as well as in the arrangement through a structural analysis based on the 1948 recording and its transcription. Negracha is innovative because its repetitive melodic and rhythmical structures are not organized according to the characteristics of traditional tangos. Pugliese composes a piece with an idea alien to the thematic contrast that is typical of the genre, creating an almost monothematic form from a few materials built around rhythmical and melodic ostinatos. Regarding aesthetic concerns, we establish possible links between Pugliese’s piece and later developmental trends –which would confirm his contribution to the genre– and we propose musical analysis as a trigger for new creations in the field of River Plate tango.
Keywords: Pugliese; tango; Negracha; composition; innovation